A rare diiodo-L-tyrosine copper(II) complexes – Crystal and molecular structure of materials stabilized by weak interactions. (1st June 2022) - Wojciechowska, Agnieszka; de Graaf, Coen; Rojek, Tomasz; Jerzykiewicz, Maria; Malik, Magdalena; Gągor, Anna; Duczmal, Marek
Graphical abstract: Highlights: Two inorganic–organic hybrid copper(II) complexes with l -I2 TyrOH have been synthesized. The copper(II) geometry is stabilized by π···π stacking, copper(II)···π and π···I interactions. The copper(II) geometry is a square pyramid with contribution of ground state of d x 2− y 2 orbital. Abstract: The problem in formation of 3, 5-diiodo-L -tyrosinato (L-I2 Tyr) various metal ion complexes as a crystals is generated by the low solubility of iodo-L -tyrosinato derivatives (as ligands) in pure aqueous solution. However, two inorganic–organic hybrid l -I2 Tyr copper(II) complexes i.e. [CuCl(L-I2 TyrOH)(phen)]∙2H2 O (1 ) and [Cu(l -I2 TyrOH)(H2 O)(phen)](NO3 ) (2 ) with l -I2 TyrOH were isolated in acid aqueous/methanol medium. In crystals 1 and 2, the monomeric distorted square planar pyramidal copper(II) coordination is stabilized by weak intramolecular π···π stacking, copper(II)···π and π···I non-covalent interactions. The connection of adjacent 2D layers into 3D supramolecular network is realised by weak π···π contacts in 1, while in 2 the 3D architecture is stabilized by weak CH···π interaction as well as π···π contacts. The complexes are also characterized by infrared and Raman spectroscopies (FT-IR, FT-Raman), X- and Q-band electron paramagnetic resonance spectroscopy (EPR), electronic spectroscopy (NIR-Vis-UV), magnetic method, and theoretical calculation.